SISTEM INFORMASI MANAJEMEN KOMPLAIN FASILITAS PERUSAHAAN PADA PT. MATTEL INDONESIA BERBASIS WEB - Norma Renita (Antivirus : Jurnal Ilmiah Teknik Informatika, 2021)
The complaint management system for company facilities is still ineffective because complaints are submitted manually through the complaint form and must be delivered directly to the engineering facility. In this case the facilities are supporting activities within the company, of course. In terms of delivering and handling complaints it is expected to be easier so that repairs are made quickly. Because of these constraints the authors intend to conduct research aimed at providing solutions through the study of various theories and observations in the field in the framework of developing existing systems in the company. The system development methodology that I use is the Waterfall methodology that refers to the SDLC (System Development Life Cycle) method, which consists of plan, analysis, design, implementation, and maintenance. The application is built based on the web using a PHP program, with a database using MySQL. The results of the development of a complaint management information system are needed in the company to optimize performance and streamline the time required. The development of a complaint management information system using the SDLC concept is very precise, this is evident from the results of tests that have been carried out with fast and accurate calculations. This system still has many shortcomings, therefore constructive input and suggestions are always expected by the author for the sake of improvement in the future.